Debt Financing And Firm Performance On Manufacturing Companies Listed On the IDX - Dian Ratu Hayati; Maisya Liztiara; Susy Muchtar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
In this period, the manufacturing sector itself recorded a growth of 6.91% despite being under pressure due to the COVID-19 pandemic. Therefore, this study was conducted to determine the effect of debt financing and firm performance on manufacturing companies. The sample used was 21 companies listed on the Indonesia Stock Exchange for the period 2016 - 2020. The sampling technique used was purposive sampling and the analytical method used was panel data regression. The results of this study state that the Short term debt ratio (STDA) has no effect on Return on Assets, Long term debt ratio (LTDA) has a negative and significant effect on Return on assets, Sales Growth (GROWTH) has a positive and significant effect on Return on assets, Short term debt ratio (STDA) has no effect on Net Profit Margin, Long term debt ratio (LTDA) has a negative and significant effect on Net Profit Margin, Sales Growth (GROWTH) has a positive and significant effect on Net Profit Margin.